Largazole and Its Derivatives Selectively Inhibit Ubiquitin Activating Enzyme (E1) - Ungermannova, Dana; Parker, Seth J.; Nasveschuk, Christopher G.; Wang, Wei; Quade, Bettina; Zhang, Gan; Kuchta, Robert D.; Phillips, Andrew J.; Liu, Xuedong (PLOS ONE, 2012)
Protein ubiquitination plays an important role in the regulation of almost every aspect of eukaryotic cellular function; therefore, its destabilization is often observed in most human diseases and cancers. Consequently, developing inhibitors of the ubiquitination system for the treatment of cancer has been a recent area of interest. Currently, only a few classes of compounds have been discovered to inhibit the ubiquitin-activating enzyme (E1) and only one class is relatively selective in E1 inhibition in cells. We now report that Largazole and its ester and ketone analogs selectively inhibit ubiquitin conjugation to p27Kip1 and TRF1 in vitro. The inhibitory activity of these small molecules on ubiquitin conjugation has been traced to their inhibition of the ubiquitin E1 enzyme. To further dissect the mechanism of E1 inhibition, we analyzed the effects of these inhibitors on each of the two steps of E1 activation. We show that Largazole and its derivatives specifically inhibit the adenylation step of the E1 reaction while having no effect on thioester bond formation between ubiquitin and E1. E1 inhibition appears to be specific to human E1 as Largazole ketone fails to inhibit the activation of Uba1p, a homolog of E1 in Schizosaccharomyces pombe. Moreover, Largazole analogs do not significantly inhibit SUMO E1. Thus, Largazole and select analogs are a novel class of ubiquitin E1 inhibitors and valuable tools for studying ubiquitination in vitro. This class of compounds could be further developed and potentially be a useful tool in cells.